IDENTIFICATION OF M4 GAMMA IRRADIATED MAIZE MUTANT BASED ON RAPD MARKERS - Rustikawati, Rustikawati; Suprijono, Eko; Romeida, Atra; Herison, Catur; Sutjahjo, Surjono H. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Gamma irradiation to induce mutation in plant has been used intensively since several decades ago. On maize, 275 Gy gamma irradiation have been known to increase genetic variability indicated by their morphological variation. Identification on genetic changes by molecular technique is important to answer whether there is mutation happening on DNA level of the plants. The objective of this research was to identify RAPD marker polymorphism on gamma irradiation mutants compared to their parents. The initial step of the research was to select random primers could positively amplify the maize DNA. The result showed that selection on 60 random primers yielded 15 primers that positively amplified the maize DNA. Amplification on both mutants and their parents by those 15 selected primers indicated that only 5 primers yielding polymorphism between mutants and their parents. Polymorphisms on mutant G1, G3 and G6 were detected on one locus, meanwhile on mutant G7, G8 and G9 were on two loci.